Atrophy and microglial distribution in primary progressive aphasia with transactive response DNA‐binding protein‐43 kDa. Issue 6 (24th May 2018) - Kim, Garam; Bolbolan, Kabriya; Gefen, Tamar; Weintraub, Sandra; Bigio, Eileen H.; Rogalski, Emily; Mesulam, Marek‐Marsel; Geula, Changiz
Abstract : Objective: To quantitatively determine the density and distribution of activated microglia across cortical regions and hemispheres in the brains of primary progressive aphasia (PPA) participants with pathological diagnoses of frontotemporal lobar degeneration with transactive response DNA‐binding protein‐43 (TDP‐43) inclusions and to examine the relationships between microglial densities, patterns of focal atrophy, (TDP‐43) inclusions, and clinical phenotype. Methods: Activated microglia and TDP‐43 inclusions were visualized in whole‐hemisphere brain sections using immunohistochemical methods from five participants with PPA‐TDP. Unbiased stereology was used to bilaterally quantify human leuckocyte antigen/D related–positive activated microglia and TDP‐43 inclusions across five language‐related regions. Density and distribution of both markers were compared across cortical regions and hemispheres, and their relationships to patterns of focal atrophy and clinical phenotype were determined. Results: Activated microglia displayed asymmetric distribution favoring the language‐dominant hemisphere, consistent with greater postmortem and/or in vivo atrophy in that hemisphere, in PPA‐TDP. In one participant with no asymmetric atrophy, quantitative distribution of microglia also lacked asymmetry. Patterns of microglial activation also showed variation that favored areas of high atrophy in regions affiliated with language function, demonstrating concordance between patterns of microglial activation, atrophy, and clinical phenotype. TDP‐43 also showed higher inclusion densities in areas of high atrophy than in regions with low atrophy, but no clear relationship with microglia density at a regional level. Interpretation: The initial activation of microglia is most likely a response to cortical abnormalities in PPA‐TDP, which contribute to atrophy. The patterns of microglial activation, TDP‐43 inclusion deposition, atrophy, and clinical phenotype suggest that activated microglia may make unique contributions to cortical thinning and TDP‐43 inclusion formation. Ann Neurol 2018;83:1096–1104